Targeting integrins and enhanced permeability and retention (EPR) effect for optical imaging of oral cancer - Keereweer, Stijn; Mol, Isabel M.; Kerrebijn, Jeroen D.F.; Van Driel, Pieter B.A.A.; Xie, Bangwen; Baatenburg de Jong, Robert J.; Vahrmeijer, Alexander L.; Löwik, Clemens W.G.M. (Journal of surgical oncology, 2012)
Background and Objectives Near‐infrared (NIR) fluorescence optical imaging is a promising technique to assess the tumor margins during cancer surgery. This technique requires targeting by specific fluorescence agents to differentiate tumor from normal surrounding tissue. We assessed the feasibility of cancer detection using NIR fluorescence agents that target either αvβ3 integrins or the enhanced permeability and retention (EPR) effect in an orthotopic mouse model of oral cancer. Methods Binding of the integrin‐targeted agent to tumor cells was assessed in vitro. Oral cancer was induced in 6 BALB/c nu/nu mice by submucosal inoculation of human OSC19‐luc cells into the tongue. Tumor growth was followed with bioluminescence imaging. A combination of agents targeting integrins or EPR effect was injected followed by fluorescence imaging in vivo and ex vivo after resection of the tongues. Results Oral cancer was clearly demarcated in vitro; in vivo; and on histological analysis with sufficient tumor‐to‐background ratios of the contrast agents. Conclusion This study demonstrates the feasibility of optical imaging of oral squamous cell carcinoma based on targeting of αvβ3 integrins and the EPR effect. Once these NIR fluorescence agents become available for clinical testing, optical image‐guided surgery could reduce residual disease after oral cancer surgery. J. Surg. Oncol. 2012; 105:714–718. © 2011 Wiley Periodicals, Inc.